Changes in body composition (muscle mass and adipose tissue) among adolescents aged 11–15 from Kraków during the COVID-19 pandemic - Artymiak, Paulina; Żegleń, Magdalena; Kryst, Łukasz (Anthropological Review, 2025)
Study aim: To assess changes in body composition, specifically focusing on muscle mass and adipose tissue, among adolescents aged 11–15 in Kraków during the COVID-19 pandemic. Materials and Methods: Cross-sectional studies were conducted in four selected districts of the city of Kraków in the years 2020 and 2022 (before and after the COVID-19 pandemic). The study group included adolescents aged 11–15 years. The percentage of body fat (%BF) was measured using the bioimpedance method. Additionally, measurements of height, arm circumference, and skinfold thickness of triceps were taken using a skinfold calliper. The collected data were used to calculate the Corrected Arm Muscle Area (CAMA). The normality of the distribution of each feature was assessed using the Shapiro-Wilk test. Statistical analysis was performed to compare differences between groups using two-way ANOVA with Tukey’s HSD post-hoc test or the Kruskal-Wallis test. Results: Among girls, a decrease in muscle mass was observed in most age categories. The opposite trend was observed among boys, as an increase in muscle mass was observed in most of the age groups. Girls were characterized by a decrease in the %BF in all cohorts, while in boys, an increase in the %BF was observed among 11,13 and 15-year-olds. In most age groups, there was an increase in the average muscle mass and increase in the %BF depending on BMI (Body Mass Index) categories in both sexes. Conclusions: This study found no notable variances in muscle mass and %BF within the examined group amid the COVID-19 pandemic. While certain outcomes indicated regression, possibly linked to reduced physical activity or prolonged sedentary periods, not all research findings exhibited decline. This could be attributed to online physical activity or enhanced dietary habits.